Application of multiplexing technology to the analysis of the intrathecally released immunoglobulins against B. burgdorferi antigens in neuroborreliosis - Zajkowska, Joanna; Lelental, Natalia; Kulakowska, Alina; Mroczko, Barbara; Pancewicz, Slawomir; Bucki, Robert; Kornhuber, Johannes; Lewczuk, Piotr (Immunology Letters, 2015)
Lyme neuroborreliosis (LNB) is an infectious disease of the nervous system caused by the tick-borne spirochete Borrelia burgdorferi. The presence of B. burgdorferi specific antibodies in cerebrospinal fluid (CSF), with evidence of intrathecal production, is the traditional diagnostic standard, although has limitations it such as low sensitivity in the very early phase. In the current study, 27 patients with possible neuroborreliosis suffered from clinically defined Bannwarth syndrome. The control group (CON) consisted of 6 patients. The analyses included function of the blood-CSF barrier (QAlb) as well as intrathecal synthesis of total IgG and IgM, (QIgG, and QIgM). Multiplexing analyses of the specific antibodies (IgG and IgM) against B.burgdorferi antigens were performed with the Microgen assay (Neuried, Germany). The ASI antibodies (Antibody Synthesis Index) specific to particular B. burgdorferi antigens (VlsE, OspC, etc.) were calculated analogously as QIgG and QIgM for separate antibody. All but one patient with NB had pathologic ASI-IgG against B. burgdorferi (median 6.3). Out of 27 NB patients, 13 had measurable ASI-IgM, and all these indices were pathologic. None of the CON subjects had pathologic ASI in either IgG or IgM class. Furthermore, NB patients showed dysfunction of the blood-CSF barrier (average QAlb in the NB and CON groups: 13.8 and 5.6, respectively, p<0.01). Twenty-one of 27 NB patients had at least one positive (>1.5) IgG-ASI against either VlsE, p100, p58, p39, p18, or OspC, and none of these patients showed positive OspA-IgG-ASI. Interestingly, the NB patient with negative IgG ASI on ELISA had the highest p100 IgG ASI on multiplexing (270.8). Among the 13 NB patients with detectable IgM-ASI on ELISA, nine showed measurable IgM-ASI against at least one antigen; however, in one of these cases, the OspC ASI was normal (0.6). In addition, one subject with non-measurable IgM ASI on ELISA had highly pathologic (19.7) index for OspC B. g. on multiplexing. The control subjects with measurable ASI-IgG on ELISA (two cases) had measurable, but normal, indices for VlsE in the IgG class also on multiplexing. None of the control subjects had measurable indices for any of the antigens in the IgM class. The simultaneous analysis of a panel of antibodies against different B. burgdorferi antigens makes multiplexing technology a very interesting supplement to the classic ELISA by providing more specific, antigen-related indices to the general, antigen-unspecific ASI. Whether this additional information proves to be diagnostically relevant will be certainly a matter of further studies.
EVALuna2:23700